Myth of King Arthur as a Conceptual Matrix for Understanding Brexit - A. A. Sharapkova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article analyses media discourse characterized by appealing to the myth about King Arthur against the background of the political crisis in the UK (Brexit). The publications of the British press in 2016-2019, online polls and blogs served as a material. Applying both linguistic and conceptual analysis, we identify the stages the myth about King Arthur gets gradually actualized. Cognitive mechanisms that get profiled at each stage are considered. Three stages of myth actualization are distinguished: (1) from using the idiom about the search for the Holy Grail in politics to comparing Brexit with finding a magic artifact, (2) comparing crisis participants with other elements of the myth, (3) modeling the way out of the crisis through the description of the search for a new leader. Particular attention is paid to how the individual elements of the myth work in dynamics. For example, it is shown that the image of the Grail undergoes an axiological reassessment from positive to negative as attitudes toward political events and figures change. We conclude that in times of crisis, society turns to national mythology, reinterprets it within a new context.